European University of Tirana Faculty of Social Sciences - Pham, Thao (Mediterranean Journal of Social Sciences, 2012)
Spain and Morocco have had a long and tumultuous relationship. Spanish culture, like Moroccan and other societies in theMediterranean area, used to place a high value on family honor and female chastity. However, the death of the Spanish dictator andSpain's entrance into the European Union have drastically changed Spanish culture and further expand the cultural and political gulfbetween these two countries. For Moroccan immigrant women in Spain, virginity remains important for Islamic marriages becauseMoroccan grooms and their families can still demand proof of virginity to validate the union. Nevertheless, young Moroccan women stillpartake in the sexual freedom granted in Spain and other European countries. Sexual experimenting, however, comes with a price. Inorder to mask evidence of behaviors that have strayed from the cultural dicta, Moroccan women would request for certificates of virginityor hymen reconstruction surgeries to maintain their family honor. Drawn from ethnographic data, interviews, and textual and discourseanalysis, this paper addresses the controversy related to the need to preserve honor and female chastity in Spain and the Spanishinstitutions' reaction to this need.